ANALISIS PEMUNGUTAN, EFEKTIVITAS DAN KONTRIBUSI PAJAK MINERAL BUKAN LOGAM DAN BATUAN TERHADAP PENDAPATAN ASLI DAERAH KOTA TOMOHON - Rambitan, Rivo Reynard; Elim, Inggriani; Pangerapan, Sonny (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Non-metallic mineral and rock tax is one of the original source of income in Tomohon. This research was conducted to find out how the analysis of pollution from Non Metallic Mineral and Rock Tax and how big the effectiveness and contribution of Mineral Non-Metals and Rocks Tax on the Original Income of Tomohon City. The method of analysis used in this research is descriptive method. The result showed that procedures and procedures for collecting non âmetallic minerals and rock taxes in Tomohon City are based on Local Regulation (Perda) No. 43 of 2012 and the effectiveness of Non-Metallic Mineral and Stone Taxes in Tomohon Municipality in 2014 is quite effective, by 2015 effective, 2016 is ineffectiveand in 2017 less effective with an average of 54,97%. While the Non-Metallic Mineral and Non-Metallic Mineral Revenue Contribution to the Tomohon Districâs Revenue in 2014 to 2017 is very less with an average of 0,94%. Keywords: Mineral Tax, Collection, Effectiveness, Contribution, Local Original Income